The Feasibility and Validity of PROMIS: A Novel Measure of Quality of Life among Children with Cleft Lip and Palate. Issue 4 (October 2016) - Ranganathan, Kavitha; Shapiro, Danielle; Carlozzi, Noelle E.; Baker, Michaella; Vercler, Christian J.; Kasten, Steven J.; Warschausky, Seth A.; Buchman, Steven R.; Waljee, Jennifer F.
Abstract : Background: Health-related quality of life is inconsistently captured among children with cleft lip and palate. The Patient-Reported Outcomes Measurement Information System (PROMIS) captures health-related quality of life, with the added benefit of comparability across clinical conditions. In this study, the authors define the validity and feasibility of PROMIS among children with clefts. Methods: Children with cleft lip and palate who were at least 5 years old and able to complete instruments independently were eligible for inclusion ( n = 93). Children completed PROMIS anxiety, depression, and peer relationship item banks as short forms or computerized adaptive tests. Participants also completed the Pediatric Quality of Life Inventory. Construct validity was measured by Spearman correlations between PROMIS and the Pediatric Quality of Life Inventory controlling for race, sex, age, and income. Feasibility was measured using instrument completion time, reading level, and floor/ceiling effects. Results: PROMIS computerized adaptive tests (peer relationship, r = 0.49; depression, r = −0.56; and anxiety, r = −0.36) and short forms (peer relationship, r = 0.65; depression, r = −0.54; and anxiety, r = −0.56) demonstrated moderate correlation with the Pediatric Quality of Life Inventory. Computerized adaptive tests had fewer floor (0 percent versus 0 percent) and ceiling (8.6 to 19.3 percent versus 21.8 to 41.9 percent) effects than short forms, and demonstrated better readability. Computerized adaptive tests required more time than short forms (peer relationship, 0.84 ± 0.67 versus 1.3 ± 0.92; depression, 0.52 ± 0.38 versus 1.1 ± 0.73; and anxiety, 0.53 ± 0.23 versus 1.1 ± 0.62; p = 0.001), as each computerized adaptive test included on average four more questions. Conclusions: PROMIS correlates well with the Pediatric Quality of Life Inventory and demonstrates similar accuracy, with better readability and efficiency. Use of PROMIS will improve our ability to compare children with cleft lip and palate to diverse populations and clinical conditions. CLINICAL QUESTION/LEVEL OF EVIDENCE: Diagnostic, II.